Perkembangan PT. Pindad Dan Pemenuhan Minimumessential Force (MEF) Dalam Perspektif Keamanan Kawasan Asia Tenggara - Shiddiqy, Muhammad Arsy Ash; Sukma, Anissa Nur; Rahmawati, Siti (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
Development of PT. Pindad, as one of the main producers of defense and security equipment in Indonesia, plays an important role in the country's efforts to fulfill the Minimum Essential Force (MEF) policy. MEF policy aims toensure that Indonesia's military forces have the minimum capabilities necessary to defend state sovereignty and maintain regional stability. In the context of security in Southeast Asia, the role of PT. Pindad is becoming increasingly significant considering the geopolitical dynamics and security threats that are developing in this region. This studyanalyzes the development of PT. Pindad in increasing production capacity and technological innovation, as well as its impact on MEF fulfillment. Apart from that, this research also explores the contribution of PT. Pindad in supporting national defense policy and its implications for regional security in Southeast Asia. Using a qualitative analysis approach, the findings of this research show that increasing the capacity and quality of PT. Pindad contributes positively to fulfilling the MEF and strengthening Indonesia's strategic position in efforts to maintain regional stability and security.